2022
DOI: 10.17979/ejge.2022.11.1.7564
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and organizational commitment: the mediating role of organizational culture

Abstract: This study seeks to determine the impact of corporate governance dimensions (compliance with the corporate governance code, top management, control environment, transparency and disclosure, rights of shareholders and stakeholders) on the three main types of organizational commitment, (affective, continuance and normative). It also aims at examining the impact of organizational culture, as an intermediate variable, on the relationship between the two above mentioned variables. The sample of this study comprised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…Furthermore, the inclusion of commitment (yellow) could be regarded as a valuable component of governance practice, given its limited frequency and overall connection strength. This is further corroborated by prior studies which indicated that the governance of an institution was impacted by the level of commitment (Najm et al , 2022; Nor et al , 2022).…”
Section: Finding and Analysissupporting
confidence: 81%
“…Furthermore, the inclusion of commitment (yellow) could be regarded as a valuable component of governance practice, given its limited frequency and overall connection strength. This is further corroborated by prior studies which indicated that the governance of an institution was impacted by the level of commitment (Najm et al , 2022; Nor et al , 2022).…”
Section: Finding and Analysissupporting
confidence: 81%